2011
DOI: 10.1016/j.cgh.2010.10.035
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence and Predictors of 30-Day Readmission Among Patients Hospitalized for Advanced Liver Disease

Abstract: BACKGROUND & AIMS The rate of readmission to the hospital 30 days after discharge (30-day readmission rate) is used as a quality measure for hospitalized patients, but it has not been studied adequately for patients with advanced liver disease. We investigated the incidence and factors that predict this rate and its relationship with mortality at 90 days. METHODS We analyzed data from patients with advanced liver disease who were hospitalized to an inpatient hepatology service at 2 large academic medical cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
130
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 28 publications
(21 reference statements)
13
130
5
1
Order By: Relevance
“…Even after excluding the patients with very early readmissions (as we did in our primary analysis), 14% were readmitted in the subsequent 3 weeks. These results are broadly consistent with other data from patients with cirrhosis (1)(2)(3) and similar to those reported for patients with CHF. (4,11) In contrast, the mortality rate in the first 30 days after discharge-8.5% overall and 4.6% after excluding deaths that occurred within the first 7 days-was higher in our patients with cirrhosis than the rates reported for patients with CHF ( 4.0%), (27) underlining the higher burden of cirrhosis for patients as well as the health care system.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Even after excluding the patients with very early readmissions (as we did in our primary analysis), 14% were readmitted in the subsequent 3 weeks. These results are broadly consistent with other data from patients with cirrhosis (1)(2)(3) and similar to those reported for patients with CHF. (4,11) In contrast, the mortality rate in the first 30 days after discharge-8.5% overall and 4.6% after excluding deaths that occurred within the first 7 days-was higher in our patients with cirrhosis than the rates reported for patients with CHF ( 4.0%), (27) underlining the higher burden of cirrhosis for patients as well as the health care system.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately 20% of patients with cirrhosis who have been hospitalized get readmitted to the hospital within the first 30 days after discharge, with substantial implications for outcomes and cost of care. (1)(2)(3) Hospital readmission is a problem that is not unique to patients with cirrhosis. (4-6) Readmission rates and consequently readmission reduction programs have been a major focus of recent quality improvement initiatives across many chronic conditions.…”
mentioning
confidence: 99%
“…Our readmission rates of 32% are consistent with those of previous studies from single tertiary‐care centers 1, 2. A report of a multistate population‐based cohort study showed the 30‐day rate of readmission to be only 12.9% 4.…”
Section: Discussionsupporting
confidence: 90%
“…The unscheduled readmission rates for patients with cirrhosis are reported to range from 20% to 37% at 30 days and up to 53% at 90 days 1, 2, 3. A high readmission rate is believed to be predicted by the severity of liver disease as determined by the Model for End‐Stage Liver Disease (MELD) score and comorbidities 1, 2, 3. These data, however, come from tertiary care referral centers where readmissions may occur outside the tertiary care health system.…”
Section: Introductionmentioning
confidence: 99%
“…(1)(2)(3) Hospitalization is a marker for a variety of poor outcomes including readmission and death. Although we are gaining a better understanding of risk factors for readmission in discharged patients, (1,(4)(5)(6) we lack a practical prognostic model to identify those at highest risk for 3-month postdischarge mortality.Identifying this group would facilitate interventions that include more intensive follow-up and consideration of early liver transplant when available. Moreover, an estimation of the probability of survival can help to inform the type of integrated palliative support that is provided to patients.…”
mentioning
confidence: 99%